RELIABILITY ANALYSIS OF PRODUCTS BASED ON HYPOTHESES TESTING ABOUT THE VALUE OF THE WEIBULL DISTRIBUTION SHAPE PARAMETER - Ya. S. Grodzenskiy; A. N. Chesalin (Российский технологический журнал, 2016)
The analysis of the products reliability during the exploitation by testing two simple hypotheses about the value of the Weibull distribution shape parameter using the optimal sequential statistical criteria is proposed. The following sequential criteria are examined: the sequential probability ratio test (Wald criterion - SPRT), the optimal generalized sequential test (Aivazyan criterion), double sequential probability ratio test (Lorden criterion - 2-SPRT), the sequential test with parabolic boundaries (Grodzenskiy criterion). Mathematical formulas necessary for the application of these sequential criteria in practice are shown. The effectiveness of the criteria is compared by the method of the statistical modeling.